THU0199 Tofacitinib, An Oral Janus Kinase Inhibitor, in The Treatment of Rheumatoid Arthritis: Changes in Lymphocytes and Lymphocyte Subset Counts and Reversibility after Up To 8 Years of Tofacitinib Treatment. (15th July 2016) - van Vollenhoven, R.; Choy, E.; Lee, E.B.; Hazra, A.; Anisfeld, A.; Lazariciu, I.; Biswas, P.; Lamba, M.; Menon, S.; Hodge, J.; Clark, J.D.; Wang, L.; et al.
Abstract : Background: Tofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). Cytokines involved in lymphocyte development, function and homeostasis are known to signal through JAKs. Objectives: To characterise the effects of tofacitinib treatment on absolute lymphocyte counts (ALCs) and lymphocyte subset counts (LSCs) and their reversibility after treatment discontinuation. Methods: ALCs were collected as part of safety monitoring procedures throughout the tofacitinib RA clinical programme. Short-term (ST) changes were evaluated in five Phase (P) 2 studies (tofacitinib 1–30 mg twice daily [BID]; treatment duration 6 weeks–6 months). Long-term (LT) changes were assessed in an LT substudy (LSS) of NCT00413699 (study ongoing; database not locked) in which patients (pts) had received tofacitinib 5 or 10 mg BID for up to 8 years. Reversibility of changes in ALCs was evaluated in pts who permanently discontinued tofacitinib due to lymphopenia as defined by a confirmed ALC <500 cells/mm 3 . Reversibility of changes in LSCs was evaluated in a P2 study (NCT00147498 ) through a 6-week withdrawal phase after 6 weeks' tofacitinib treatment and in the LSS during a 4 week temporary withdrawal phase in pts with an ALC ≤1000 cells/mm 3 and ≥40% decrease in ALC vs baseline (NCT00413699 ). Results: In total, there were 1432 and 4867 pts from P2 and LT extension (LTE) studies, respectively. Approximately 1050 pts from LTE study NCT00413699 were enrolled into the LSS for evaluation of ALCs and LSCs (median tofacitinib exposure of 5 years). Pre-treatment baseline for natural killer (NK) cells, B cells, T cells (CD3+, CD4+ and CD8+) were available for 130, 133, 133, 52 and 52 pts, respectively. Effects of tofacitinib on ALCs and LSCs are summarised in Table 1 . Tofacitinib treatment resulted in a transient increase in ALC at Month 1, followed by a gradual decline to stabilise below baseline levels by ∼4 years. Magnitude and time course of changes in CD4+ and CD8+ T cells mirrored those of ALC. CD4+ and CD8+ cell counts were well correlated with ALC. LT treatment showed higher NK cell counts vs baseline, in contrast to decreases seen after ST dosing. B cell counts increased with ST treatment but returned toward baseline with LT treatment. Conclusions: Tofacitinib treatment was associated with decreases in ALC. Changes in CD4+ and CD8+ T cell counts were reflected in ALC, while B cell and NK cell counts tended to return to or exceed baseline levels. Reversibility is observed following ST and LT dosing. Acknowledgement: This study was sponsored by Pfizer Inc. Editorial support was provided by Claire Cridland of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: R. van Vollenhoven Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, E. Choy Grant/research support from: Amgen, Boehringer Ingelheim, Chugai Pharma, Ferring Pharmaceuticals, Novimmune, Pfizer Inc, Roche, and UCB, Speakers bureau: Amgen, Boehringer Ingelheim, Chugai Pharma, Eli Lilly, Hospira, MSD, Novartis, Pfizer Inc, Regeneron, Roche, Sanofi-Aventis, and UCB, E. B. Lee Consultant for: Pfizer Inc, A. Hazra Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Anisfeld Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, I. Lazariciu Consultant for: Pfizer Inc, Employee of: Quintiles, P. Biswas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Lamba Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Menon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Hodge Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. D. Clark Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Krishnaswami Shareholder of: Pfizer Inc, Employee of: Pfizer Inc